Ꮵ ᏣᎳᎩ (TSI Tsalagi), I am Cherokee: understanding contemporary art of the Cherokee diaspora - Holland, Ashley (My University, 2021)
Questions of diaspora and cultural identity drive my analysis of the work and lives of four contemporary ᏣᎳᎩ (Tsalagi), Cherokee, artists: Kay WalkingStick (Cherokee Nation), Luzene Hill (Eastern Band of Cherokee Indians), Brenda Mallory (Cherokee Nation), and Kade L. Twist (Cherokee Nation). I propose the shaping of an art historical understanding of these artists through the ᏣᎳᎩ worldview, ᏚᏳᎦᏛ (duyuktv), the right way. For ᏣᎳᎩ people, ᏚᏳᎦᏛ is connected to who we are in both a physical and spiritual sense. This dissertation consists of four case studies, each comprising of a unique chapter. Chapter two examines Kay WalkingStick, whose work has been discussed more through homogenized concepts of indigeneity. I argue through the use of ᏚᏳᎦᏛ for a reading of her work as that of a ᏣᎳᎩ artist. Chapter three analyzes Luzene Hill, a multi-media artist, best known for conceptual installations addressing the issue of violence against women. Hill creates works from her personal experience of a violent sexual assault. Hill became and remains a survivor fully in control, and her art displays this reality and can be understood as a representation of ᏚᏳᎦᏛ. Chapter four discusses Brenda Mallory. I argue that her work is an expression of ᏚᏳᎦᏛ through the foundational principles of the four directions. I conclude in chapter five with interdisciplinary artist Kade L. Twist. Twist looks to storytelling and language as a way to examine Indigenous issues of displacement. My overall argument for this dissertation is that when ᏣᎳᎩ experience displacement and cultural estrangement, which is counter to a ᏣᎳᎩ life in balance within the concept of ᏚᏳᎦᏛ, art is a way to reestablish ᏚᏳᎦᏛ and therefore re-engage one’s connection to community and metaphorically return home.
Keywords: art history; Cherokee; diaspora